IDENTIFIKASI JENIS LEBAH MADU ASAL KEPULAUAN SULA MENGGUNAKAN APLIKASI DNA BARCODE LCO GEN - Mas'ud, Abdu; Hasan, Said; Sundari, S. (LP4MK STKIP PGRI Lubuklinggau, 2023)
Sanana Honey is a local brand, a type of honey produced by forest bees which is well known in the Sula Islands, North Maluku. The forest bees of the Sula Islands have the potential to be developed as a producer of quality honey. At this time there has been no scientific report regarding the types and characteristics of the forest bee species from the Sula Islands. This study aims to identify the types of honey-producing forest bees by applying the LCO gene DNA barcode. The methods used in this study used: 1) DNA extraction from bee body tissues using the DNA Miniprep Kit procedure (Zymo Research, D6016); 2). DNA amplification by PCR amplification procedure with TOYOBO KOD FX Neo (KFX-201); 3) bidirectional DNA sequencing process (Bi-directional sequencing). The results showed that the specimen was successfully amplified with an amplicon size of 677 bp. Furthermore, the results of BLASTN analysis revealed that the sequence has a 97.78% similarity with the Apis cerana mitochondria complete genome gene country of Russia, but is phylogenetically different between the two.